A time-dependent model for improved biogalvanic tissue characterisation. Issue 10 (October 2015) - Chandler, J.H.; Culmer, P.R.; Jayne, D.G.; Neville, A.
Highlights Influence of load rate shown for biogalvanic characterisation of ex vivo tissue. A time-dependent biogalvanic characterisation model has been developed. Application of this model reduces the influence of external load switching rate. Tissue health discrimination has been demonstrated using the proposed model. The proposed model improves the applicability of biogalvanic method to surgery.